2020
DOI: 10.31125/hunhemsire.834195
|View full text |Cite
|
Sign up to set email alerts
|

Yaşlı Bireylerin Ağrıya Yönelik Tamamlayıcı ve Alternatif Tedavi Kullanım Durumu ve Tutumu

Abstract: Amaç: Araştırmanın amacı, yaşlı bireylerin ağrıya yönelik tamamlayıcı ve alternatif tedavi yöntemlerini kullanım durumu ve tutumunu incelemektir. Gereç ve Yöntem: Tanımlayıcı bu çalışmanın örneklemi, Kasım 2018-Nisan 2019 tarihlerinde bir eğitim araştırma hastanesinin dahiliye kliniklerinde yatan 178 yaşlı bireyden oluşmaktadır. Veriler "Birey Tanıtım Formu" ve "Tamamlayıcı Tedavileri Kullanmaya Yönelik Tutum Ölçeği (TTTÖ)" ile toplanmıştır. Bulgular: Yaşlı bireylerin %25.8'i ağrıya yönelik tamamlayıcı ve alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
0
0
2
Order By: Relevance
“…As can be seen, the mean scores of patients’ attitudes toward complementary practices differ in previous studies that were conducted with different patient groups. This is explained by the differences in individual and disease-related characteristics 16-18. In this study, it was found that the mean ASUCT score of the female gender was higher at a statistically significant level than that of the male gender ( P < .05).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…As can be seen, the mean scores of patients’ attitudes toward complementary practices differ in previous studies that were conducted with different patient groups. This is explained by the differences in individual and disease-related characteristics 16-18. In this study, it was found that the mean ASUCT score of the female gender was higher at a statistically significant level than that of the male gender ( P < .05).…”
Section: Discussionmentioning
confidence: 51%
“…In the literature review, although no study was detected evaluating the attitudes of hypertension patients toward complementary practices, it was found that there are studies examining the attitudes of individuals who have different chronic diseases and healthy individuals toward complementary practices. In a previous study, it was found that the attitudes of cancer patients toward using complementary and supportive methods were positive,16 and in another study examining the attitudes of elderly individuals toward complementary practices in pain management, the average complementary therapy attitude scores of elderly individuals was found to be low 17. In the study conducted by Ozer et al, in which the attitudes of patients who applied to the internal medicine outpatient clinic toward traditional and complementary medicine were examined, it was reported that patients had a moderate attitude toward traditional and complementary medicine 18.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…22 Sayın Kasar ve ark.nın çalışmalarında da yaşlıların %25,8'inin ağrıya yönelik tamamlayıcı ve alternatif tedavi yöntemi kullandığı belirlenmiştir. 23…”
Section: Gtt Uygulamalarinin Siniflandirilmasiunclassified
“…Yaşlı bireyler ile yapılan çalışmalarda çoğunlukla bireylerin bitkisel ürünleri tercih ettiği, bunların yanı sıra masaj, beslenme takviyesi, aromaterapi ve sıcak uygulamaları kullandıkları görülmektedir. 6,21,22,23 Yaşlılarda sıklıkla tercih edilen yöntemlerinden biri olan bitkisel ürünlerin kullanımı dikkatle ele alınmalıdır. [29][30][31] Yaşlılıkta çoklu ilaç kullanımı ile birlikte doğal bitkisel ürünlerin tercih edilmesi sonucunda beklenen terapötik cevabın abartılı olmasına ya da esas tedavinin etkinliğinin düşmesine sebep olabilmektedir.…”
Section: Yaşli Bireylerde Gtt Uygulamalarinin Etkileriunclassified